Islamic values in environmental communication within the Malaysian media : a case study of Utusan Malaysia and Berita Harian - Mohamad Saifudin Mohamad Saleh,; Shaidatul Akma Adi Kasuma,; Mark Harris Zuknik,; Nik Norma Nik Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
We argue that environmental communication within the Malaysian media landscape is influenced by Islamic beliefs and teachings. Although Islam has a great influence on environmental communication in Malaysia, it is an area underexplored by past studies. We conducted a content analysis on two mainstream Malay media outlets, namely Utusan Malaysia and Berita Harian, for a six-year period (2012-2017) in order to investigate the types of Islamic values which were represented in the environmental articles published by both newspapers. We also conducted interviews with 11 journalists from both newspapers to determine the purpose of using Islamic values in environmental articles. The result of content analysis discovered that tawhid (unity of God) is the most common Islamic value used in Utusan Malaysia’s environmental articles, while in Berita Harian, iman (faith) is the value which most commonly appears. In the interviews, journalists from Utusan Malaysia described that the value of tawhid is used the most in the environmental articles as it is one of the core values in Islam, while the journalists from Berita Harian explained that iman has been used the most as this value is an intrinsic part of the readers’ lives. However, most of the interviewees stated that the main challenge for them came from the need of the journalists themselves to have a great understanding of both Islam and environment. It is hoped that the findings of this study could serve as a reference for future research in the area of Islamic environmental communication.